2002
DOI: 10.1183/09031936.02.00273102
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related interactive effect of smoking and household pets on asthma incidence

Abstract: The authors examined the interactive effect of smoking and pets at home on the incidence of asthma and the difference between sexes.The longitudinal data from the first two cycles of the National Population Health Survey, conducted in Canada, were used. A total of 12,636 subjects who reported no asthma at baseline were included in the analysis.The 2-yr cumulative incidence of asthma was higher in females than in males. Female sex and household pets demonstrated a significant interaction in the development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 26 publications
1
26
0
4
Order By: Relevance
“…When exposed to passive tobacco smoking in utero, lung function of young males with asthma is lower than of young females with asthma [50]. Pet-owning females are more susceptible to asthma when they also smoke [22]. Lung function in females, if sensitised by cat and pollen allergens, is more affected than in males [51].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When exposed to passive tobacco smoking in utero, lung function of young males with asthma is lower than of young females with asthma [50]. Pet-owning females are more susceptible to asthma when they also smoke [22]. Lung function in females, if sensitised by cat and pollen allergens, is more affected than in males [51].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, a comprehensive preventive effect, rather than the effect of a reduction of a single exposure, is assessed. Since airway morbidity is influenced by sex [21], and sex-specific effects of environmental exposure on asthma have been reported recently [22], the clinical effectiveness of the intervention programme was evaluated separately in males and females.…”
mentioning
confidence: 99%
“…For example, the Canadian National Population Health Survey [7] reported that female smokers had a 70% higher prevalence rate of asthma compared to nonsmokers, and the interaction between smoking and sex was particularly evident among females aged ,25 yrs (OR 2.18) and among heavier as compared to lighter smokers or nonsmokers. The majority of studies that have investigated a temporal association between smoking and onset of asthma support the suggestion that smoking places an individual at a significantly increased risk of developing asthma (table 1) [10][11][12][13][14]. In an attempt to address whether smoking is a causal or a proxy risk factor, a large cohort of clinic-referred non-asthmatic adult subjects with established allergic rhinitis was investigated to determine the importance of active cigarette smoking as an additional risk factor for incident asthma at 10-yrs follow-up [15].…”
Section: Smoking As a Risk Factor For The Development Of Asthmamentioning
confidence: 99%
“…It is now recognised, however, that classification by disease severity simply suggests a static feature, which is clearly not the the interaction between smoking and sex is particularly evident among heavier smokers compared to lighter smokers or nonsmokers [6][7][8][9][10][11][12][13][14] Incident asthma Smoking is highly predictive of the development of new onset asthma in allergic adults with a clear dose-response effect of smoking exposure [15] Increased asthma morbidity and mortality Asthmatic smokers are at risk of developing more severe symptoms, higher frequency of exacerbations, and worse asthma-specific quality of life [16][17][18][19][20][21]; cigarette smoking in asthma is also associated with increased numbers of life threatening asthma attacks and greater asthma mortality [22,23] Greater asthma severity Smoking status and smoking duration are strongly related in a dose-dependent fashion to the level case in everyday clinical asthma where the level of severity varies in relation to the amount of anti-asthma medication taken. These considerations have promoted the more clinically informative concept of asthma control [52,53].…”
Section: Clinical Outcomes In Smokers With Asthmamentioning
confidence: 99%
“…As in most other studies, a higher incidence rate was also found for females (2.9 cases?1,000 person-yrs -1 ) compared with males (1.5 cases?1,000 person-yrs -1 ). Different factors, such as airway size, hormonal factor status and socioeconomic factors, have been discussed [18]. The incidence rate may also reflect a tendency among physicians to diagnose an asthma-like disorder as asthma in females and COPD in males [14].…”
Section: Discussionmentioning
confidence: 99%